PENGARUH UKURAN PERUSAHAAN,AKTIVITAS PERUSAHAAN,PRODUKTIVITAS DAN LEVERAGE TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT - Fani Apriliyani; Dirvi Surya Abbas; Imam Hidayat; Imas Kismanah (OPTIMAL Jurnal Ekonomi dan Manajemen, 2022)
The purpose of this study to determine the effect of company size, company activity, and leverage on the disclosure of sustainability reports in manufacturing companies listed on the Indonesia Stock Exchange (BEi). The research time period used is 4 years, namely the 2016-2019 period. The population of this study includes all manufacturing companies listed on the Indonesia Stock Exchange (BEi) for the period 2016-2019. The sampling technique was using purposive sampling technique. Based on the predetermined criteria, 8 company samples were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis. With the panel data regression model used is the Fixed Effect model. The results showed that company size has a statistical t value (2.518480)>t-table value (2.04841) and a prob value 0.0200 <0.05, it can be concluded that the firm size variable has a positive effect on the disclosure of sustainability reports, corporate activities are known to have a statistical t value. (-0.073586)<t-table value (2.04841) and prob value 0.9420> 0.05, it can be concluded that the corporate activity variable has no effect on the Sustainability Report disclosure and leverage has at-statistic value of-0.425259, while the t-table with a level of 5%, df (nk) = 28 of 2.04841. Thus the value of the t-statistic Leverage (-0.425259)<t-table value (2.04841) and the prob value of 0.6750> 0.05, it can be concluded that the leverage variable has no effect on sustainability report disclosure